2019
DOI: 10.1371/journal.pone.0221783
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in men and women with type 2 diabetes: A qualitative gender-sensitive exploration of barriers to smoking cessation among people with type 2 diabetes

Abstract: Objectives Despite growing evidence of the impact of smoking on diabetes complications, people with type 2 diabetes still smoke at high rates and little is known about the specific barriers to quit smoking in this group. The purpose of this article is to explore the perception of smoking, and motivation and barriers to quit among smokers with type 2 diabetes. This exploratory study will help designing a smoking cessation intervention tailored to the needs of people with type 2 diabetes. We hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 44 publications
(40 reference statements)
2
21
0
2
Order By: Relevance
“…73 74 For the present study, we will use an evidence-based smoking cessation intervention and tailor it to the participants from the findings of the previous phases of our study. 75 …”
Section: Methods and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…73 74 For the present study, we will use an evidence-based smoking cessation intervention and tailor it to the participants from the findings of the previous phases of our study. 75 …”
Section: Methods and Analysismentioning
confidence: 99%
“…This study, DISCGO-RCT (Diabetes and Smoking Cessation: a Gender-Oriented Randomised Controlled Trial) is the next phase of the DISCGO-MIX study (CER-VD project ID: 302/15, Swissethics ID PB_2016–01459) (purple area of figure 1 ; see also below for details), which is intended to define the beliefs, motivations and specific needs of diabetic smokers by using a mixed-methods approach. 75 Using qualitative methods, we explored patients with diabetes and healthcare provider’s experiences and priorities. We adapted the intervention on the basis of their comments and preferences (eg, no interest in group sessions, desire for a motivational and ‘guilt-free’ approach).…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking is also related to poor glycemic control in diabetes patients 2 . A qualitative study of type 2 diabetes patients who smoked showed that willingness to change smoking behaviors was related to personal self‐image, and meaningful engagement in life and social relationships 3 , implying a possible lack of these factors in type 2 diabetes patients who continue to smoke. As tobacco smoking is the most popular form of substance use disorders, or an addiction, the patients should be referred to evidence‐based smoking cessation therapies before it is too late.…”
Section: Figurementioning
confidence: 99%
“…Up to 65% of cardiovascular mortality is attributable to interaction between smoking and diabetes. Research suggests that diabetic people who smoke have poorer diabetes control, greater insulin needs, increased insulin resistance and increased risk of hypoglycemia [132].…”
Section: Smokers (Male) 37%mentioning
confidence: 99%